CRIMES OF GENOCIDE: AN ANALYTICAL STUDY OF THE EFFICIENCY OF INTERNATIONAL CRIMINAL LAW IN PROTECTING ETHNIC AND RELIGIOUS GROUPS (World Bulletin of Management and Law, 2024)
Express issue Protection Criminal International For groups Religious And ethnicity from Highlights Mission in the law International year, And this Importance come from necessity protection Rights Humanity And when You meet him from Violations Physical And for not Availability deterrent radical For frying from This is amazing Practices , So it was security essential from to provide protection Criminal she has from International aspect And the local , And that According to For treaties Legal that It was completed Mention it in Charters and agreements International In a way private order Basic To the court Criminal International. It is evident Problematic the study in that rights Groups Religious And ethnicity You are exposed To destroy on about comprehensive , And on Although from construction court Criminal International Concerned in accounting Perpetrators that Crimes And during this Search It becomes clear for us What is it? Protection Criminal International For rights Groups Religious And ethnicity, and rights The reserve Internationally According to The court Criminal International, and the efforts made from side The court Criminal International from Side , And For devices International Other concerned With rights This is amazing Groups from Side second .